Cellular immunotherapies for cancer. (4th May 2017) - Berraondo, Pedro; Labiano, Sara; Minute, Luna; Etxeberria, Iñaki; Vasquez, Marcos; Sanchez-Arraez, Alvaro; Teijeira, Alvaro; Melero, Ignacio
ABSTRACT: Lessons learned over decades on the use of gene and cell therapies have found clinical applicability in the field of cancer immunotherapy. On December 16 th, 2016 a symposium was held in Pamplona (Spain) to analyze and discuss the critical points for the clinical success of adoptive cell transfer strategies in cancer immunotherapy. Cellular immunotherapy is being currently exploited for the development of new cancer vaccines using ex vivo manipulated dendritic cells or to enhance the number of effector cells, transferring reinvigorated NK cells or T cells. In this meeting report, we summarize the main topics covered and provide an overview of the field of cellular immunotherapy.